2012
DOI: 10.1007/s00217-012-1729-4
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compound production in Agave duranguensis juice fermentations using four native yeasts and NH4Cl supplementation

Abstract: Nitrogen has a significant effect on the fermentation rate and the chemical composition of alcoholic beverages. Nitrogen deficiency during fermentation of Agave juice for mescal production can lead to slow fermentations and end-products with low aromatic compound variety. In this study, the effects of NH 4 Cl supplementation on volatile compound formation in Agave duranguensis juice fermented at 28°C with the native yeast strains Saccharomyces cerevisiae ITD00185, Hanseniaspora uvarum ITD00108, Torulaspora del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For each sample, 10 g was homogenized with sterile distilled water using a blender at 12,000 rpm using three 30 s pulses. The homogenate was serially diluted in sterile distilled water and spread onto each of four types of media: MEA (2% malt extract, 0.1% peptone, 2% glucose, 1.8% agar; containing 100 mg/L chloramphenicol and 100 mg/L streptomycin), LA medium (BD Co.), YDP (1% yeast extract, 1% peptone, 2% glucose, 1.8% agar; containing 100 mg/L chloramphenicol), and Gauze No.1 (AOBOX BIOTECHNOLOGY; 25 mg/L nalidixic acid and 50 mg/L cycloheximide) (Liu et al, 1996 ; Rutiaga-Quiñones et al, 2012 ). Plates were prepared for each sample and medium in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…For each sample, 10 g was homogenized with sterile distilled water using a blender at 12,000 rpm using three 30 s pulses. The homogenate was serially diluted in sterile distilled water and spread onto each of four types of media: MEA (2% malt extract, 0.1% peptone, 2% glucose, 1.8% agar; containing 100 mg/L chloramphenicol and 100 mg/L streptomycin), LA medium (BD Co.), YDP (1% yeast extract, 1% peptone, 2% glucose, 1.8% agar; containing 100 mg/L chloramphenicol), and Gauze No.1 (AOBOX BIOTECHNOLOGY; 25 mg/L nalidixic acid and 50 mg/L cycloheximide) (Liu et al, 1996 ; Rutiaga-Quiñones et al, 2012 ). Plates were prepared for each sample and medium in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Most compounds were alcohols, esters and acids. The differences in the volatile compounds, such as benzyl alcohol, hexanoic acid ethyl ester, and dodecanoic acid ethyl ester concentrations, could be attributable to the microorganisms and conditions found during the fermentation process [8,9,22]. In previous studies, Kirchmayr et al [10] identified 21 different yeast species, such as Saccharomyces cerevisiae, Kluyveromyces marxianus, Zygosaccharomyces rouxii, Z. bisporus, Torulaspora delbrueckii, and Pichia membranifaciens, and 27 different bacterial species during fermentation in artisan mezcal production.…”
Section: Volatile Compounds In Mezcal From a Angustifolia By Place Omentioning
confidence: 99%
“…Among the factors that have an influence on the artisanal process of making mezcal are Agave species and origin [2,4,7], initial sugar concentration, environmental conditions, native yeast strain, and, in certain cases, the addition of ammonium sulfate or ammonium chloride to the fermentation must [4,6,[8][9][10]. Another important parameter that ultimately defines the quality of agave beverages is the distillation system used [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published research on fermentations of agaves suggests that non-Saccharomyces yeasts have an important role in the initial fermentation process and influence the production of the volatile compounds (Lappe-Oliveras et al 2008;Narváez-Zapata et al 2010;Martell Nevárez et al 2011). The potential use of these yeasts as inoculants has been described (Rodríguez-Sifuentes et al 2014;Nuñez-Guerrero et al 2016), as well as their participation in generating the volatile compounds in mescal, mainly esters (Martell Nevárez et al 2011;Rutiaga-Quiñones et al 2012;Hernández-Carbajal et al 2013). Despite the increasing use of non-Saccharomyces yeasts in biotechnology, there are still many opportunities to improve native yeast exploration.…”
Section: Introductionmentioning
confidence: 99%